"The old country and the new world order the relevance of Aristotle's theory of comedy on the selected works of Harold Pinter and Alan Bennett" - Henson, Maria Pilar S. (2009)
The comic theory found in Aristotle's Poetics and the related scholarship accumulated throughout the centuries form what are customarily considered as the attributes of comedy - the Ludicrous, a plot based on probability rather than historical accuracy, low characters, and an ending where nobody slays or is slain. However, the applicability of the Poetics as a critical tool is often limited to Menandrean comedies and later varieties. The comedies of Harold Pinter and Alan Bennett are among the important works of the twentieth century, which would initially seem too eccentric and quite removed from Aristotle's comic theories. Nevertheless, this thesis attempts to prove that Pinter and Bennett are inheritors of a comic tradition that can be traced as far back as the Poetics. Chapter I explains that this study is significant in that the selected plays of Pinter and Bennett are viewed from an entirely comic perspective. Earlier analyses of their works tend to focus on their post-modern aspect, psychological implications, and the influence of absurdist drama, and are inclined to overlook the comic elements of their work. A reevaluation of Aristotle's comic principles also need to be undertaken in the light of new translations of the Poetics and pertinent scholarly works produced in this century. Chapter II discusses Aristotle's theory of comedy. It provides a historical background for Attic comedies and the adoption of Aristotle's theories in England. The discussion in the Poetics on the nuances of characterization is applied to the ludicrous personages of comedy. Twentieth century scholars have reexamined the text of the Poetics and came up with interpretations that question that definition of comedy as a species of the Ludicrous that is not painful or destructive, the function of language in drama, the idea of a proper comic ending, and the conception of plot as a series of causally linked complications that are all neatly resolved in the end. Chapter III analyzes the selected works of Pinter and Bennett within the framework of the Aristotelian comic tradition. The comedies chosen for this paper are mostly short plays, character studies whose structures are similar to the early forms of Attic comedy - the monologues, the satire and marriage comedies. The simplicity of these plays clearly shows how plot, character and language contribute to the whole idea of the play. They deal with common experiences such as eating, cleaning the house, receiving visitors, and attending a party. They also demonstrate how Aristotle's ideas on comedy have evolved throughout the centuries. Chapter IV concludes by reiterating the influence of Aristotle's comic theory to the works of Pinter and Bennett: the imitation of the action of lower types with the exaggeration of their flaws; the adherence to the principles of cohesiveness and poetic probability; the concepts of anagnorisis and the three unities; and the use of plot, character, thought and diction, in analyzing the comic text. At the same time, these comedies question the idea of "painless" comedy, happy endings, and the purpose of language solely to express the thoughts and objectives of characters. These departures from Aristotle's comic precepts reflect ideas that are recognized in the period within which these plays were written and the contribution of Pinter and Bennett to the development of the comic genre.
Thesis (M.A. English Studies : Anglo-American Literature)--University of the Philippines Diliman.
Keywords: Pinter, Harold; Bennett, Alan